Effects of wearing compression stockings on exercise performance and associated indicators: A systematic review - Mota, G. R.; Simim, M. A. M.; Santos, I. A.; Sasaki, J. E.; Marocolo, M. (Open Access Journal of Sports Medicine, 2020)
This systematic review investigated the effects of wearing below-knee compression stockings (CS) on exercise performance (or sports activity) and associated physiological and perceived indicators. We searched articles on PubMed using the following terms: "graduated compression stockings"; "compression stockings"; "graduated compression socks"; "compression socks" combined with "performance", "athletes", "exercise", "exercise performance", "fatigue", "sports" and "recovery", resulting in 1067 papers. After checking for inclusion criteria (e.g., original studies, healthy subjects, performance analysis), 21 studies were selected and analyzed. We conclude that wearing CS during exercise improved performance in a small number of studies. However, wearing CS could benefit muscle function indicators and perceived muscle soreness during the recovery period. Future research should investigate the chronic effect of CS on Sports Medicine and athletic performance.